Analisis Swot Dan Promosi Kerajinan Bambu Desa Wisata Brajan Kabupaten Sleman Yogyakarta - Heni Widyaningsih - AKPAR BSI Yogyakarta (Universitas Bina Sarana Informatika, 2012)
ABSTRACT - Brajan tourism village is located in Sendang Agung, Minggir, Sleman, Yogyakarta, Indonesia. The origin of this village's name adapted from the name Kyai Brojo Setiko. Although Brajan is just a small village, but the community has had craft not only in Indonesia but has to penetrate the international market. The typical work of this village is a Brajan bamboo handicraft. Bamboo craft is what brings the Village Brajan become more developed until now recognized as a tourism village. Tourists can visit to study the creation of works of bamboo as well as to buy souvenirs and handicraft of bamboo in Brajan. In this research, the subjects of study were 3 owner’s bamboo handicraft in Brajan. while the object of study was the bamboo handicraft in Brajan.This research is aimed to increase the promotion and marketing strategy. In today's, promoting product and service via internet technology using social media networking becomes a massive trend among youth all over the world. The internet technology enables business owner to run sales promotion and deliver 24-hours service toward their customer. Unfortunately, Dusun Brajan which is popular with bamboo handicraft do not have the knowledge to utilize internet technology and social media networking as media promotion. UII in collaboration with PT Jasa Rahardja have been working seriously promoting Brajan bamboo handicraft. The five strategy Brajan bamboo handicraft to go international are tourist attraction, tourism sapta pesona, indirect export, SWOT analysis, promotion and on-line marketing.Key Word: SWOT analysis, promotion, tourism village